The Mediterranean species of genus Loxosceles Heineken & Lowe, 1832 (Araneae: Sicariidae): Loxosceles imazighen sp. n. from Morocco and first description of the female of L. mrazig Ribera & Planas, 2009 from Tunisia - Massa, Marc; Ribera, Carles (Zootaxa, 2021)
The aim of this paper is to describe a new species of the genus Loxosceles Heineken & Lowe, 1832 from Morocco, Loxosceles imazighen sp. n., and to describe for the first time a female of Loxoxceles mrazig Ribera & Planas, 2009 from Tunisia. Both species live in xeric and desert environments and are located in southern Atlas Range. Molecular phylogenetic analyses, using mitochondrial (cox1, 16S) and nuclear (H3, 28S) markers, revel that these species are closely related and that they constitute a separate evolutionary lineage of L. rufescens (Dufour, 1820) and of the set of endemic species of the Canary Islands. L. imazighen sp. n. differs from L. mrazig, the closest species morphologically and geographically, in the shapes and proportions of the male palpal tibia and the shapes and dispositions of the female seminal receptacles. In addition, L. mrazig females show morphological variability in their genitalia, mainly in the inner and outer lobes. Although that variability cannot be associated with different populations, since it also appears within individual populations, and is not related to genetic or geographic distances.